2017
DOI: 10.1590/s1519-99402017000200013
|View full text |Cite
|
Sign up to set email alerts
|

Performance, carcass parameters, meat quality and lipid profile from feedlot young bulls fed cottonseed

Abstract: SUMMARY The objective of this study was to evaluate the performance, carcass, meat quality, fatty acid profile and liver alterations of cattle supplemented with cottonseed feedlot. It used 100 Nelore cattle, being divided into two groups of 50 animals, which received a cottonseed (CS) in grain form by the diet in the proportion of 15% and the other group was provided with control diet without CS in the feedlot for 88 days. The diets were isoprotein and isoenergetic and concentrate:roughage ratio of 60:40. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
1
1
2
Order By: Relevance
“…There was no influence of cottonseed supplementation on color parameters indicated by the tasters; moreover, other authors have reported no negative influence of cottonseed or other byproducts used for feeding cattle on the sensorial attributes of beef (Eiras et al, 2017;Gomes et al, 2016;Polizel Neto et al, 2022). Despite the physicochemical analysis of the raw beef revealed a change in the objective meat color and pH (pH 24 h), there was an increase in the yellowness index (higher value of b*) and a decrease in pH, similar to the results reported by Esteves et al (2017). Similarly, Stelzleni et al (2013) investigated the influence of objective color parameters of beef from finished heifers fed cottonseed pellets (which yielded a lower brightness index), and no differences in meat quality or sensory traits were reported.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…There was no influence of cottonseed supplementation on color parameters indicated by the tasters; moreover, other authors have reported no negative influence of cottonseed or other byproducts used for feeding cattle on the sensorial attributes of beef (Eiras et al, 2017;Gomes et al, 2016;Polizel Neto et al, 2022). Despite the physicochemical analysis of the raw beef revealed a change in the objective meat color and pH (pH 24 h), there was an increase in the yellowness index (higher value of b*) and a decrease in pH, similar to the results reported by Esteves et al (2017). Similarly, Stelzleni et al (2013) investigated the influence of objective color parameters of beef from finished heifers fed cottonseed pellets (which yielded a lower brightness index), and no differences in meat quality or sensory traits were reported.…”
Section: Resultssupporting
confidence: 84%
“…The main factor is associated with this change in lipid composition because an increase in the C18:2w6 (linoleic acid) content could be responsible for the oxidation of compounds associated with characteristic meat flavors or undesirable flavors (Ferrinho et al, 2018). In contrast, in beef in the present study, there were no effects on ether extract or fatty acid composition (Esteves et al, 2017). This could be associated with the lower level of cottonseed feed provided to the animals in the present study, which is not sufficient to change the fatty acid profile of the meat.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations